Analisis Untuk Melakukan Pada Suatu Optimalisasi Inovasi Kinerja Pegawai Serta Peran Jabatan Di Dinas Sumber Daya Air Marga Dan Bina Kontruksi Lubuk Pakam Kabupaten Deli Serdang - Saragih, Siti Khofifah; Nurbaiti, Nurbaiti (LPPM Universitas Labuhanbatu, 2022)
This article was written with the intention of maximizing the analysis of the skin and hair in the Dinas Sumber Daya Air Marga and Bina Kontruksi Lubuk Pakam Deli Serdang. The competence of an inspector (aparatur) is a variable that, is responsible for determining how to handle a particular incident. There are a number of independent factors that contribute to a person's level of education, technical proficiency, and quality of life, as well as the possibility of employment. One example of this is the inspection apparatus Kabupaten Deli Serdang, which employs 41 people. Using this method, Dinas Sumber Daya Air Marga and Bina Kontruksi Lubuk Pakam Deli Serdang will use the best possible kinerja pegawai and peran jabatan. No, this can also be done during the process of building a house when more than one building is completed. This study's findings can be deduced from the fact that it primarily affects the use of mass-produced apparatus. Nevertheless, the first tingkatan consists of numerous days that are superior. The aforementioned. Additionally, 75% of those surveyed were from the PNS. Additionally, 25% of those who fall into the honorer category In addition, it results in kinerja and jabatan-related information.